Theoretical strength and homogeneous sliding in metallic glass: exactly solvable model - Lazarev Nikolai; Bakai Alexander (Journal of the Mechanical Behavior of Materials, 2013)
At low temperature, T→0, the yield stress of a perfect crystal is equal to its so-called theoretical strength. The yield stress of nonperfect crystals is controlled by the stress threshold of dislocation mobility. A noncrystalline solid has neither an ideal structure nor gliding dislocations. Its yield stress, that is, the stress at which the macroscopic inelastic deformation starts, depends on distribution of local, attributed to each atomic site, critical stresses at which the local inelastic deformation occurs. We describe exactly solvable model of planar layer strength and sliding with an arbitrary homogeneous distribution of local critical stresses. The rate of the thermally activated sliding is closely related to parameters of the low-temperature strength. The sliding activation volume scales with the applied external stress as where β<1. The proposed model accounts for mechanisms and the yield stress of the low-temperature deformation of polycluster metallic glasses, because intercluster boundaries of a polycluster metallic glass are natural sliding layers of the described type.